2019
DOI: 10.1074/jbc.ra119.009610
|View full text |Cite
|
Sign up to set email alerts
|

Structural insight into metallocofactor maturation in carbon monoxide dehydrogenase

Abstract: The nickel-dependent carbon monoxide dehydrogenase (CODH) employs a unique heterometallic Ni-Fe-S cluster, termed the C-cluster, to catalyze the interconversion of CO and CO2. Like other complex metalloenzymes, CODH requires dedicated assembly machinery to form the fully intact and functional C-cluster. In particular, nickel incorporation into the C-cluster depends on the maturation factor CooC; however, the mechanism of nickel insertion remains poorly understood. Here, we compare X-ray structures (1.50-2.48 Å… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…Two conserved cysteines from each monomer are involved in Ni coordination [36]. That the CODH produced in the absence of CooC cannot be activated by exogenous Ni shows that CooC is not just involved in the delivery of the metal, but also in the preparation of the active site for receiving the nickel [37] This is consistent with our previous investigation of Dv CODH [18,30]. Our data show that the CODHs matured in the presence of either CooC1 or CooC2, which share ~ 40 % identity (SI Figure S9), have similar values of activity and nickel content.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Two conserved cysteines from each monomer are involved in Ni coordination [36]. That the CODH produced in the absence of CooC cannot be activated by exogenous Ni shows that CooC is not just involved in the delivery of the metal, but also in the preparation of the active site for receiving the nickel [37] This is consistent with our previous investigation of Dv CODH [18,30]. Our data show that the CODHs matured in the presence of either CooC1 or CooC2, which share ~ 40 % identity (SI Figure S9), have similar values of activity and nickel content.…”
Section: Discussionsupporting
confidence: 85%
“…The Ni-free C cluster of CooS2 is very similar to the C cluster of Ch CODH II (PDB ID: 3B53) [14] and Dv CODH (PDB ID: 6B6X) [12] with the only apparent difference being the missing Ni ion, while the remaining parts of the C cluster are almost unchanged ( figure 3). The Ni-free C cluster of CooS2 also resembles the [3Fe-4S]-Fe 1 site of the C cluster of CODHs produced without CooC (Dv CODH -CooC ) or devoid of the D cluster (Dv CODH(ΔD) +CooC ), neither of which can be activated by incubation with Ni [30].…”
Section: Active Sitementioning
confidence: 99%
“…There have been previously published examples of the use of site directed mutagenesis to interconvert [3Fe-4S] and [4Fe-4S] clusters in enzymes, 29 but this is the first report of [2Fe-2S] to [4Fe-4S] cluster conversion as a result of protein engineering. The as-isolated C45G/T50C variant contains half as much Ni per monomer as the WT enzyme, consistent with the previously demonstrated role of the D-cluster in mediating redox chemistry during nickel incorporation, 30 but after activation with NiCl 2 under reducing conditions, the activity of the C45G/T50C variant is similar to that of the WT enzyme.…”
Section: Discussionsupporting
confidence: 87%
“…If the C‐cluster precursor is a classical Fe 4 S 4 cubane cluster, as shown by spectroscopic studies, nickel insertion would imply bond breaking, involving His265 and Cys300. Very recent structural studies on CODH from Desulfovibrio vulgaris ( Dv CODH) revealed the great plasticity of the C‐cluster and are in agreement with the “bond breaking” theory, with His266 (His265 in Rr CODH) and Cys302 (Cys300 in Rr CODH) serving as the nickel binding site before its transfer to its stable active site (Figure a . In Dv CODH, the d ‐cluster is a Fe 2 S 2 center that would be involved in nickel insertion by mediating electron transfer, working in concert with CooC to control the redox state of the active site, ensuring thus the right metalation of the cluster.…”
Section: Metallocenter Biosynthesissupporting
confidence: 56%
“…(a) Proposed mechanism for CODH maturation: Fe and S atoms are first inserted to form a classical [Fe 4 S 4 ] cluster. The following steps remain unclear to yield the active C‐cluster (adapted from Reference ). (b) Proposed mechanism for ACS maturation (adapted from Reference )…”
Section: Metallocenter Biosynthesismentioning
confidence: 99%